Berenstain Bears: on the job (The) - Berenstain, Stan (New York : Random House, 1987)
Two young bears speculate on all the things they could grow up to be, including a bus driver, farmer, scientist, singer, and computer programmer.
Keywords: Occupations-Fiction; Bears - Fiction; Stories in rhyme